INFECÇÕES NATURAIS POR HELMINTOS EM PERDIZES (RHYNCHOTUS RUFESCENS TEMMINCK, 1815) DE CATIVEIRO, NO MUNICÍPIO DE JABOTICABAL, ESTADO DE SÃO PAULO - Mapeli, E.b. [UNESP] (2024)
Redwinged tinamou - Rhynchotus rufescens - is a neotropical tinamiform bird. Captive breeding has expanded considerably in Brazil, although studies on endoparasites of tinamiforms are scarce and most of them approach have only dealt with helminth systematics. The objective of this study was to acquire knowledge about indicators of helminthic infection in a captive population sample with 15 adult birds, from Jaboticabal, Sao Paulo state. Necropsies were performed after the death of birds. Helminths were collected and identified. After this phase, indicators of helminthic infection such as prevalence, mean intensity, variation on intensity and abundance were calculated. A total of 2,428 helminths were identified as Subulura olympioi, Capillaria penidoi and Paratanaisia confusa, with prevalence of 26%, 100% and 33%, respectively.